Knowledge, attitude and practice of hepatitis (B) among healthcare workers in relation to their vaccination status in Khartoum, Sudan, 2015: a cross-sectional study - Mustafa, Almustafa Siddig Mohammed; Ahmed, Almegdad Sharafaldin Mohamed; Alamin, Tariq Ahmed Abdelbaset; Shaheen, Mutaz Tarig HassanAhmed; Hilali, Awab Mohamed Mohamed Ahmed; Fadul, Moneeb Hassan Mohammed Alamin; Abdelsalam, Ahmed Abdelaziz Abugrain; Abdelrahim, Mohamed Ahmed Sidahmed; Elsheikh, Mohamed Nasr Mohamed Ahmed (Sudan Journal of Medical Sciences, 2018)
Background: Hepatitis B is a serious chronic infection of the liver and caused by hepatitis B virus. It is an endemic disease in Sudan. Healthcare workers are occupationally more prone to acquire the disease. Evaluation of their knowledge, attitude and practice and their vaccination status, are very important in the control of the disease. The aim of this study was to assess the knowledge, attitude, and practice of healthcare workers towards hepatitis B and their vaccination status. Materials and Methods: In total, 372 healthcare workers were enrolled in the study, which was conducted at 10 public hospitals in Khartoum state during July-August 2015. After taking written informed consent from the Khartoum State Research Department, self-administrated questionnaires were distributed to the healthcare workers. The KAP score was the sum of the three categories, which is 32 points, and the mean was then obtained. Results: The study revealed that the respondents’ mean scores of knowledge, attitude, and practice (KAP) were 18.4, 2.14 and 2.49, respectively. The study also showed that doctors have the highest KAP score in comparison with other occupations. Doctors are the least occupational category that uses gloves when dealing with patient’s blood. The KAP score was found higher among vaccinated healthcare workers 27.4% in comparison to unvaccinated ones, That yield to a significant the association between KAP score and vac-cination status (p-value0.007). Conclusions: This study concluded that, there is a positive association between the level of vaccination among Health care workers and their Knowledge, attitude and practice of hepatitis B virus. Further studies would be recommended on larger population.